HEPATIC INVOLVEMENT IN RHEUMATOID ARTHRITIS: CAUSES, COMORBIDITIES, AND CLINICAL IMPLICATIONS - Sękulski, Marcin; Mrozek, Martyna; Zydlewski, Igor; Blecharczyk, Małgorzata; Pacanowska-Trawnicka, Martyna; Jakubiec, Paweł (International Journal of Innovative Technologies in Social Science, 2026)
Aim: The aim of the study is to summarize the current knowledge on the causes of liver dysfunction in patients with rheumatoid arthritis (RA), with particular emphasis on viral infections, nonalcoholic fatty liver disease (NAFLD), autoimmune liver diseases, and treatment-related hepatotoxicity. Methods: A review of the literature published between 2015 and 2025 was conducted using PubMed and Google Scholar. Studies on hepatic complications in patients with RA were analyzed. Additional relevant studies were identified through reference screening, and selection was based on titles and abstracts. Results: In RA, liver dysfunction mainly reflects comorbid liver disease and metabolic risk rather than drug toxicity. NAFLD is the most frequent hepatic abnormality in RA, with a prevalence exceeding the general population, strongly associated with obesity, insulin resistance, and inflammatory activity. Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections remain clinically relevant due to their potential to mimic or modify RA manifestations and the risk of reactivation during immunosuppressive therapy. Autoimmune liver diseases occur less frequently, though primary biliary cholangitis (PBC) is reported more often in RA than in the general population. Methotrexate (MTX) most commonly causes transient, reversible enzyme abnormalities. Biological therapies and Janus kinase (JAK) inhibitors have varied liver safety profiles, with HBV reactivation in patients without adequate prophylaxis remaining a key concern. Conclusion: Liver dysfunction in RA reflects coexisting liver disease, chronic inflammation or immunogenetic predisposition. Safe long-term management requires regular liver function assessment, mandatory HBV and HCV screening, and identification of metabolic risk factors to minimize hepatic complications.